Study of Association of Various Psychiatric Disorders in Brain Tumors - Sharma, Achal; Das, Anand Kumar; Jain, Akhilesh; Purohit, Devendra Kumar; Solanki, Ram Kumar; Gupta, Ajay (Asian Journal of Neurosurgery, 2022)
Background Brain tumors may be associated with high morbidity, and psychiatric symptoms may be an early manifestation. It is important to address mental symptoms as early as possible because they are prone to develop psychiatric comorbidities in future. If untreated, these situations may worsen and lead to burden upon caregivers.Methods A total of 176 brain tumor patients between January 2021 and January 2022 constituted the sample size. All recently diagnosed cases of brain tumor with age equal to or more than 18 years who can comprehend and answer questionnaires were included. Patients with a long history of brain tumor or who had a history of a psychiatric illness other than presenting symptoms or any other serious medical illness were excluded.Results Twenty-seven percent of brain tumor patients had psychiatric symptoms. Depressive symptoms were the most common, associated with 24% of patients, followed by anxiety disorders. Psychiatric disorders were more common in supratentorial compared to infratentorial tumors. Psychiatric symptoms seem to be associated more commonly with malignant tumors and peritumoral edema. Among malignant tumors, depressive symptoms tend to be related with high-grade glioma, and among benign tumors, they were more common in meningioma. No predilection to laterality and anatomical lobe involvement is reported.Conclusion Screening of psychiatric disorders should be a routine in brain tumor patients. An integrated approach is required to treat brain tumor patients. Healthcare professionals should be more vigilant about the onset of psychiatric symptoms and the need of palliative care to improve the quality of life.
Keywords: psychiatric; SCAN; brain tumors; depressive disorders; anxiety